Evaluating the student experience at UK-China joint institutes - Lee, Christine H.; Bremner, Duncan; Clerkin, Caoimhe; Daw, Michael I.; Hussain, Sajjad; McDonald, Pip; Menzies, John; Meyer, John Christopher; Ponciano, Joao; Shan, Sofia; Shipston, Michael J.; Welburn, Susan C.; et al. (Frontiers in Education, 2024)
Joint Institutions are created from two different universities joining together to create a collaborative research and education effort. Compared to traditional universities, several unique challenges present themselves from this arrangement. We are especially interested in the student experience at UK-China Joint Institutes. We therefore organized a conference with the UK-China Joint Institute Alliance to aggregate knowledge on this issue. This paper summarizes the topics presented and discussed at the conference including: student learning and methods with which to measure and improve it, monitoring and incentivizing student engagement, the transition period from high school to university, teaching evaluations of staff, and lastly, learning and teaching during the COVID-19 pandemic.